Concentrations of glutamate and N-acetylaspartate detected by magnetic resonance spectroscopy in the rat hippocampus correlate with hippocampal-dependent spatial memory performance - Duarte, João M. N. (Frontiers in Molecular Neuroscience, 2024)
Magnetic resonance spectroscopy (MRS) has been employed to investigate brain metabolite concentrations in vivo, and they vary during neuronal activation, across brain activity states, or upon disease with neurological impact. Whether resting brain metabolites correlate with functioning in behavioral tasks remains to be demonstrated in any of the widely used rodent models. This study tested the hypothesis that, in the absence of neurological disease or injury, the performance in a hippocampal-dependent memory task is correlated with the hippocampal levels of metabolites that are mainly synthesized in neurons, namely N-acetylaspartate (NAA), glutamate and GABA. Experimentally naïve rats were tested for hippocampal-dependent spatial memory performance by measuring spontaneous alternation in the Y-maze, followed by anatomical magnetic resonance imaging (MRI) and magnetic resonance spectroscopy (MRS) in the hippocampus and cortex. Memory performance correlated with hippocampal concentrations of NAA (p = 0.024) and glutamate (p = 0.014) but not GABA. Concentrations of glutamate in the cortex also correlated with spatial memory (p = 0.035). In addition, memory performance was also correlated with the relative volume of the hippocampus (p = 0.041). Altogether, this exploratory study suggests that levels of the neuronal maker NAA and the main excitatory neurotransmitter glutamate are associated with physiological functional capacity.